IMPLEMENTASI PEMBELAJARAN PAI BERBASIS TASAWUF UNTUK MEMBENTUK KARAKTER ISLAMI PESERTA DIDIK DI SMAN 1 KINALI - Suharjo Suharjo; Alizar Alizar; Yusratul Hayati (ADISAM PUBLISHER, 2024)
This study aims to examine the learning strategy of Islamic Religious Education (PAI) based on Sufism in developing the Islamic character of students at SMAN 1 Kinali. The method used is descriptive-qualitative with a case study. Data were obtained through observation, interviews, and documentation. Data analysis was carried out through data reduction, data presentation, and drawing conclusions. The results of the study indicate that SMAN 1 Kinali applies two strategies in learning PAI based on Sufism to develop the Islamic character of students, namely: 1) Direct strategy using the targhib wa tarhib method (motivation and threat), persuasive, and 2) Indirect strategy through habituation of worship, role models, and discipline and respect for others. The application of this strategy has proven effective in forming the Islamic character of students, such as obedience to worship, honesty, discipline, and social concern